2004
DOI: 10.1021/es034680s
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Oxidation of Hg0to HgBr2in the Troposphere

Abstract: The oxidation of elemental mercury (Hg0) to the divalent gaseous mercury dibromide (HgBr2) has been proposed to account for the removal of Hg0 during depletion events in the springtime Arctic. The mechanism of this process is explored in this paper by theoretical calculations of the relevant rate coefficients. Rice-Ramsberger-Kassel-Marcus (RRKM) theory, together with ab initio quantum calculations where required, are used to estimate the following: recombination rate coefficients of Hg with Br, I, and O; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
332
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(351 citation statements)
references
References 27 publications
12
332
7
Order By: Relevance
“…Previous laboratory studies reported apparent rate coefficients in the range of (3.6 ± 0.9) × 10 −13 to (3.2 ± 0.3) × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [19,20,22]. Theoretical studies estimated the rate constants to be from 9.8 × 10 −13 to 2.1 × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [3,21,23]. Theoretical and experimental rate constants for mercury oxidation by Br and Cl atoms at 298 K have previously been compared in detail in Table A.2 by Subir et al [18].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 97%
“…Previous laboratory studies reported apparent rate coefficients in the range of (3.6 ± 0.9) × 10 −13 to (3.2 ± 0.3) × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [19,20,22]. Theoretical studies estimated the rate constants to be from 9.8 × 10 −13 to 2.1 × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [3,21,23]. Theoretical and experimental rate constants for mercury oxidation by Br and Cl atoms at 298 K have previously been compared in detail in Table A.2 by Subir et al [18].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 97%
“…Laboratory kinetic studies imply that the global mean lifetime of Hg 0 is 120 -210 days against oxidation by OH [Sommar et al, 2001;Pal and Ariya, 2004a] and 60-1500 days against oxidation by O 3 [Hall, 1995;Pal and Ariya, 2004b]. However, in light of the expected rapid thermal dissociation of HgOH [Goodsite et al, 2004], Calvert and Lindberg [2005] concluded that oxidation of Hg 0 by OH is much slower than reported by the above studies and is insignificant under atmospheric conditions. Atmospheric observations constrain the residence time of total atmospheric mercury (Hg 0 + Hg(II)) to 0.5-2 years [Schroeder and Munthe, 1998], which places an upper limit on the lifetime of Hg 0 against oxidation (depending on competition between reduction and deposition of Hg(II)).…”
mentioning
confidence: 89%
“…[4] Goodsite et al [2004] developed a homogeneous mechanism for Hg-Br chemistry in the troposphere based on theoretical kinetic calculations, and showed that gasphase oxidation of Hg 0 by Br atoms could explain mercury depletion events (MDEs) in the Arctic springtime boundary layer. They suggested that this mechanism would be important more generally in the marine boundary layer and on the global scale.…”
mentioning
confidence: 99%
See 2 more Smart Citations